Actor modelling and its contributions to the development of integrative strategies for management of pharmaceuticals in drinking water - Titz, Alexandra; Döll, Petra (Social science & medicine, 2009)
Widespread presence of human pharmaceuticals in water resources across the globe is documented. While some, but certainly not enough, research on the occurrence, fate and effect of pharmaceuticals in water resources has been carried out, a holistic risk management strategy is missing. The transdisciplinary research project "start" aimed to develop an integrative strategy by the participation of experts representing key actors in the problem field "pharmaceuticals in drinking water". In this paper, we describe a novel modelling method, actor modelling with the semi-quantitative software DANA (Dynamic Actor Network Analysis), and its application in support of identifying an integrative risk management strategy. Based on the individual perceptions of different actors, the approach allows the identification of optimal strategies. Actors' perceptions were elicited by participatory model building and interviews, and were then modelled in perception graphs. Actor modelling indicated that an integrative strategy that targets environmentally-responsible prescription, therapy, and disposal of pharmaceuticals on one hand, and the development of environmentally-friendly pharmaceuticals on the other hand, will likely be most effective for reducing the occurrence of pharmaceuticals in drinking water (at least in Germany where the study was performed). However, unlike most other actors, the pharmaceutical industry itself does not perceive that the production of environmentally-friendly pharmaceuticals is an action that helps to achieve its goals, but contends that continued development of highly active pharmaceutical ingredients will help to reduce the occurrence of pharmaceuticals in the water cycle. Investment in advanced waste or drinking water treatment is opposed by both the wastewater treatment company and the drinking water supplier, and is not mentioned as appropriate by the other actors. According to our experience, actor modelling is a useful method to suggest effective and realisable integrative risk management strategies in complex problem fields that involve many societal actors. © 2008 Elsevier Ltd. All rights reserve
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IG.zentr.actorm_0
Keywords: Actor modelling; DANA (Dynamic Actor Network Analysis); Drinking water; Germany; Pharmaceuticals; Risk management strategy

Das subsaharische Afrika: Entwicklungsdynamiken, Herausforderungen, Lösungsversuche - Krüger, Fred; Drescher, Axel; Louis, Norman; Titz, Alexandra (Geographische Rundschau, 2019)
In recent years, the pace and multiplicity of development dynamics in Sub-Saharan Africa has increased such that new explanatory approaches are needed to assess the spatial, economic and social transformation and propose adequate solutions to tackle poverty and vulnerability. Demographic scenarios indicate that Sub-Saharan societies will have to face a wide range of challenges in the coming decades. European development policies, Chinese economic intervention, or a new African urbanism serve as examples to highlight the diverse transformation that is currently affecting everyday livelihoods in Sub-Saharan Africa.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Human Development Index (HDI); Globaler Süden; fragmentierende Entwicklung; HDI; Human Development Index

Geographies of doing nothing–internal displacement and practices of post-disaster recovery in urban areas of the Kathmandu valley, Nepal - Titz, Alexandra (Social Sciences, 2021)
Disaster-related internal displacement is on the rise in many countries and is increasingly becoming an urban phenomenon. For many people, as in the case of the earthquake disaster 2015 in Nepal, protracted or multiple disaster displacements are a lived reality. While the drivers of displacement are relatively well understood, significant uncertainties remain regarding the factors that trigger prolonged or secondary displacement and impede ending of displacement or achieving durable solutions. The purpose of this article is to illustrate and theorise the discourse of reconstruction and return that shapes experiences, strategies, and policies in order to gain a better understanding of the obstacles to pursuing durable solutions that are still shaping the reality of life for urban internally displaced people (IDPs) in Kathmandu Valley. I use the concepts of ‘fields of practice’ and ‘disaster justice’ to provide insights into the theorisation of the links between social inequality, structural forms of governance, and the reconstruction process itself. Findings demonstrate that the application of these concepts has great potential to expand our understanding of ‘realities of life’ and practices of IDPs, and thus contribute to a more differentiated evidence base for the development and implementation of appropriate disaster risk reduction policies and practices.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Disaster justice; Disaster risk reduction (DRR); Earthquake disaster; Fields of practice; Internal displacement; Long-term displacement; Waiting

Kulturgeographisches Geländepraktikum – Leitfaden. Erlanger Skripte zum Geographiestudium - Gebauer, Matthias; Geiselhart, Klaus; Fürmaier, Peter; Haferburg, Christoph; Kaplan, Lena; Kieslinger, Julia; Kordel, Stefan; Kress, Martina; Lendl, Jonas; Orlowski, Benedikt Marko; Pohle, Perdita; Schnorr, Kristina; et al. (2015)

Manoeuvring barriers: Assessing adaptive strategies for and persistent barriers to urban Nature-based Solutions in Lilongwe, Malawi - Bauer, Willi; Titz, Alexandra (Nature-Based Solutions, 2025)
Urban Nature-based Solutions (NbS) are increasingly promoted globally as a multifunctional and cost-effective way to address social and environmental challenges in cities. Based on these premises, there is a growing municipal interest in promoting NbS in cities of the so-called 'Global South'. However, current research is still clearly biased towards the 'Global North', with particularly few studies focusing on cities in Sub-Saharan Africa (SSA). As a result of these research gaps, there is a high risk that maladapted NbS – modelled on examples from other regions that do not meet local requirements and needs – will be adopted. Against this background, this article examines barriers to the adoption of urban Nature-based Solutions and the opportunities for successful implementation of NbS in cities in Malawi. Drawing on qualitative data (workshops, narrative expert interviews, group discussions) collected during five research stays in Lilongwe (2022–2024), the article outlines and analyses in detail the strategies employed to overcome these barriers by those actors in charge for implementing the Lilongwe Ecological Corridor Initiative (LECI), a large-scale NbS in the country's capital city. By empirically exploring the particularities of the implementation of the LECI, the article characterises features of NbS in SSA rarely explored in other contexts, such as the reframing of existing greenspaces, the pragmatic adaptation of NbS-plans and the formulation of by-laws as part of their planning. These insights can serve as a basis for further conceptual developments and critical engagement and to promote a deeper understanding of the potentials and pitfalls of implementation strategies seeking to manoeuvre persistent barriers.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Adaptive strategies; Barriers; Lilongwe Ecological corridor initiative; Malawi; Nature-based Solutions; Urban greening

Natural hazards and hazard management in Nepal Naturgefahren und Naturgefahrenmanagement in Nepal - Titz, Alexandra (Geographische Rundschau, 2011)

Naturgefahren als Entwicklungshemmnis - Titz, Alexandra (Praxis Geographie, 2012)

Naturgefahren und Naturgefahrenmanagement im Oberen Paznauntal/Tirol. - Titz, Alexandra; Grießinger, Jussi (Mitteilungen der Fränkischen Geographischen Gesellschaft Band 61/62, 2016)
Naturgefahren wie Hochwasser, Massenbewegungen, Lawinen oder Erdbeben fordern alljährlich zahlreiche Menschenleben und verursachen Schäden in Milliardenhöhe. Die Bedrohung durch die Natur hat sich in den letzten Jahrhunderten nicht grundlegend geändert, dennoch war und ist der Umgang mit Naturgefahren einem stetigen Wandel unterworfen. Trotz der präzisen Erforschung der geophysikalischen Prozesse und Innovationen im technischen Bereich, die neben einer verbesserten Vorhersage, Frühwarnung und Kommunikation auch effektivere Schutzmaßnahmen ermöglichen, scheint die Verwundbarkeit und Risikoanfälligkeit der Menschen in gleichem Maße anzuwachsen. Am Beispiel der Alpengemeinde Galtür in Tirol/Österreich, in der sich 1999 ein schweres  Lawinenereignis zutrug, soll der Umgang mit Naturgefahren exemplarisch nachgezeichnet werden. Dazu fließen auch Ergebnisse eines projektorientierten Hauptseminars ein, die Studierende der Bachelorstudiengänge Kulturgeographie und Physische Geographie im Rahmen von empirischen Erhebungen und Expertengesprächen vor Ort in Galtür gewonnen haben.
Keywords: Naturgefahren; Naturgefahrenmanagement; Geographische Hazardforschung; Alpen; Paznauntal; Galtür; Lawine; Gefahrenzonenplan

Naturgefahren und Naturrisiken im Nepal-Himalaya. Eine geographische Analyse von Ursachen, Auswirkungen und der Wirksamkeit von Schutzmaßnahmen - Titz, Alexandra (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
UnivIS-Import:2016-07-26:Pub.2005.nat.dgeo.IG.zentr.naturg

Pathways for sustainable and inclusive cities in Southern and Eastern Africa through Urban green infrastructure? - Titz, Alexandra; Chiotha, Sosten S. (Sustainability, 2019)
Cities in sub-Saharan Africa are currently confronted with a multitude, and hitherto unexperienced, magnitude of transformative phenomena such as rising inequality, exclusion, poverty and increased residency in informal settlements. These stressors are posing challenges to cities in terms of housing, infrastructure and provision of basic services as well as climate change adaptation. Despite the high dynamics and novel characteristics of city transformation, this urban transition seems to take place rather 'quietly' and has, so far, obviously hardly been understood or appreciated by researchers and governments. Subsequently, the multifaceted and extremely challenging problems associated with the process of urbanisation cannot be adequately addressed. Green infrastructure (GI) is currently emerging as a concept for cost-effective urban sustainability and livelihood security. Preservation and provision of accessible urban green spaces is increasingly recognised as an essential part of the liveability of cities. Extensive literature review revealed that the systematic integration of GI concepts in urban planning is seen by an increasing number of researchers as an essential approach to tackle major current and future challenges. Based on the literature review, we suggest that broadening the concept of urban GI by linking it to governance and rights-based conceptualisations will have the potential to unlock more resourceful paths for sustainable, green, and inclusive urban development of cities in Southern and Eastern Africa.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Food security; Inclusive cities; Livelihood security; Resilient cities; Right to the city; Sub-Saharan African cities; Sustainable cities; Urban agriculture; Urban green infrastructure; Urbanisation

Sustainable Livelihood in Southern Mustang District - Haffner, Willibald; Benachib, Hafida; Brock, Christoph; Gerique-Zipfel, Andres; Merl, Kerstin; Morkel, Silke; Park, Martina; Pohle, Perdita; Titz, Alexandra; Werning, Knut (Translating Development. The case of Nepal., 2003)
UnivIS-Import:2015-04-20:Pub.2003.nat.dgeo.IG.zentr.sustai

The bus rapid transit (BRT) in Dar es Salaam: A pilot study on critical infrastructure, sustainable urban development and livelihoods - Krüger, Fred; Titz, Alexandra; Arndt, Raphael; Gross, Franziska; Mehrbach, Franziska; Pajung, Vanessa; Suda, Lorenz; Wadenstorfer, Martina; Wimmer, Laura (Sustainability, 2021)
Inner-city transportation looms large in big cities in the so-called Global South due to rapid population and urban growth. To tackle this challenge, a Bus Rapid Transit (BRT) system was implemented in Dar es Salaam (Tanzania) in 2016. This paper reports on the results of a pilot study on the impacts of the BRT on city development and livelihoods in Dar. Our pilot study, which is part of the collaborative research project LIPSINDAR (Linking Partners for a Sustainable and Inclusive Dar es Salaam), was not designed to provide a comprehensive insight into the problems of urban planning, infrastructure modification and their impact on urban livelihoods. Rather, using the example of Dar es Salaam, the study served as an entry point to highlight challenges and future research demands in the context of urban insecurities and risks in large cities of the Global South. In particular, our study investigated the BRT as an element of critical infrastructure in Dar es Salaam and probed into its impact on residents’ livelihoods, focusing on the influence of service disruptions on everyday routines, and on different stakeholders’ views on the functionality of the BRT. Elaborating on this topic, interviews, street vendor surveys and mappings were used as methods to describe the processes. To examine the results more closely, the outcome was divided into groups of different fields of activity, namely Traffic Management, Local Residents, City Administration, Basic Provision Services and Street Vendors. In summary, the pilot study confirms that the implementation of the BRT system has, in general, served to improve urban livelihoods. Reducing commuting times and enhancing access to basic services found positive results. There is, however, still potential for improvement: the bus network, in particular, needs to be expanded and the vulnerability to natural extreme events, especially flooding, needs to be addressed.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Critical infrastructure; Criticality; Eastern Africa; Inclusiveness; Infrastructure; Livelihoods; Risk; Society; Sub-saharan Africa; Sustainability; Transportation; Urban resilience

The myth of community? - Titz, Alexandra; Krüger, Fred; Cannon, Terry; et al. (World Disasters Report 2014. Focus on Culture and Risk, 2014)

Tracing the urbanisation of risk in Malawi: A multilevel analysis - Bauer, Willi; Titz, Alexandra; Manda, Mtafu C. (Jàmbá, 2024)
Cities in Malawi have long been outside the focus of disaster risk reduction. As a result, urban risks remain poorly understood, and urban governments and disaster risk reduction (DRR) practitioners working in cities struggle to adequately support vulnerable urban populations. This is evidenced by recent disasters such as Cyclone Freddy, which devastated the city of Blantyre in 2023, and increasingly common small-scale events in urban areas. This article analyses the Malawian city as a distinct riskscape, shaped by national-level policies of neglect that create an institutional void that DRR practitioners working at the city level struggle to fill. This process is complicated by a multitude of challenges at different levels of governance, especially leaving small-scale events prevalent in urban areas largely unaddressed. This process of risk accumulation is increasingly affecting urban residents. Methodologically, we demonstrate this through a comprehensive policy analysis and by drawing on expert and civil society interviews and questionnaires conducted in Lilongwe City. Contribution: By outlining the interlocking challenges at multiple levels and grounding them in empirical data, we highlight the specificities of urban DRR efforts in Malawi and provide opportunities to improve them.
CRIS-Team Scopus Importer:2024-09-20
Keywords: disaster risk reduction; global south; governance; Malawi; multilevel analysis; urban vulnerability

Uncovering "Community': Challenging an Elusive Concept in Development and Disaster Related Work - Titz, Alexandra; Cannon, Terry; Krüger, Fred (Societies, 2018)
In all areas of academic or practical work related to disaster risk, climate change and development more generally, community and its adjunct community-based have become the default terminology when referring to the local level or working with the people'. The terms are applied extensively to highlight what is believed to be a people-centred, participatory, or grassroot-level approach. Today, despite, or because of, its inherent ambiguity, community' tends to be used almost inflationarily. This paper aims to analyse the way the concept of community' has come into fashion, and to critically reflect on the problems that come with it. We are raising significant doubts about the usefulness of community' in development- and disaster-related work. Our approach is to first consider how community' has become popular in research and with humanitarian agencies and other organisations based on what can be considered a moral licence' that supposedly guarantees that the actions being taken are genuinely people-centred and ethically justified. We then explore several theoretical approaches to community', highlight the vast scope of different (and contested) views on what community' entails, and explain how community' is framing practical attempts to mitigate vulnerability and inequity. We demonstrate how these attempts are usually futile, and sometimes harmful, due to the blurriness of community' concepts and their inherent failure to address the root causes of vulnerability. From two antagonistic positions, we finally advocate more meaningful ways to acknowledge vulnerable people's views and needs appropriately.
Created from Fastlane, WoS look-up

USA Regional: Der Mittlere Westen - Dynamische Veränderungen im Herzen der USA - Fuchs, Stephan; Gerhard, Ulrike; Krüger, Fred; Titz, Alexandra (Geographische Rundschau, 2015)

USA regional: Mythos und Alltagskultur – der Mittlere Westen - Krüger, Fred; Titz, Alexandra (Kulturgeographie der USA - Eine Nation begreifen, 2017)
Bereits in der unscharfen Bezeichnung „Mittlerer Westen“ kommen die zumeist eher diffusen und räumlich schwer abgrenzbaren Vorstellungen vom großen Zentralraum der Vereinigten Staaten zum Ausdruck. Zwei unterschiedliche Leiterzählungen werden mit diesem Großraum häufig verknüpft: zum einen die Idee des amerikanischen „Heartland“ als Wiege einer von erfolgreicher Agrarkolonisation und Industrialisierung geprägten, kleinbürgerlichen US-amerikanischen Alltagskultur, zum anderen die stark mit mystifizierenden Vorstellungen aufgeladenen Assoziationen der „Frontier“ und des „Wilden Westens“, der von den Great Plains bis über den Mittleren Westen hinaus in die Bergwelten der Rocky Mountains in Wyoming und Montana ausgreift und ebenfalls Bilder des „typisch Amerikanischen“ erzeugt. Beide Meta-Erzählungen produzieren zwar gegenläufige, jedoch gleichermaßen romantisierende, stereotype Vorstellungswelten eines beschaulichen, gutbürgerlichen und fleißigen, im Herzland verorteten Amerika einerseits und einer rauen, von Freiheit, Selbstbehauptung, der Zähmung der Wildnis und der endlosen Weite der Prärie geprägten Lebenswelt andererseits. Geographisch verorten lassen sich diese Fiktionen in erster Linie in den südlichen und westlichen Teilen des Gebiets der Großen Seen (Great Lakes) und in den westlich anschließenden Great Plains. Genau dort finden sich aber auch die realen Gegenbilder dieser Erzählungen: die stark disparaten räumlichen und ökonomischen Entwicklungen in den Teilregionen des Mittleren Westens (Middle West oder Midwest) und die damit einhergehenden dynamischen Veränderungen der Lebenswelte